India's development experience - Singh, Tarlok (London : Macmillan Press Ltd, 1974)
This an in-depth country case of rationale and operational criteria-for a new national/international economic (and social) order based on comprehensive factual synthesis of policies, data, numerous major studies, and India's general experience. Topics include: regional growth and planning; human resource development; welfare; production effort in agriculture; industry objectives and performance; private corporate sector; public sector; transport objectives; domestic savings; exports; condition of growth among others.
Includes bibliographical references and index.
lje 03/10/2018
Loans
Keywords: Economic development; Economic growth .; India